Mihin suomessa tarvitaan sisä-grammeja? - Ojutkangas, Krista (Virittäjä, 2008)
When are sisä grams used in Finnish? (englanti) 3/2008 (112) WHEN ARE SIS GRAMS USED IN FINNISH? In Finnish, being inside or in close contact with something is usually expressed by means of internal locative cases, but the language also has a series of postpositions and adverbs expressing place that use the root sis. These are termed sis grams. The article looks first at the type of concrete spatial relations involved in descriptions featuring these sis grams, and how they differ from the use of internal locative cases. Examining the contexts in which the sis grams are used, the writer concludes that these lie along a continuum. She puts forward the interpretation that in addition to acting as postpositions or adverbs, these grams also have a use that can be interpreted as referential. The theoretical basis for the study is cognitive linguistics research. In spatial relationships expressed using the sis grams, it is the inside of the landmark container, not the container itself, which is of specific relevance. In this way the grams are used to describe situations in which the containment relationship between the trajector and the landmark is in some way unusual (ruoka suussa food in [your] mouth suun sisll inside the mouth). The sis grams are also used when internal locative cases would, in the same situation, be used to express that something is in close contact with, rather than inside, something else (kivi maassa stone on the ground maan sisss in the ground). Using the sis grams it is also possible to consider as containers things that are not naturally so at all (preen sisll inside the shingle/splint cf. preess on the shingle/splint). Based on the study material, the writer identifies three typical contexts in which sis grams are used: in precisely describing the location of something; in expressing contrast between two places; and in placing a trajector in a landmark in contexts where the landmark container is first constructed in the text. On the basis of the syntactic environments in which the grams are used, a continuum can be construed. This continuum runs from adpositions to plain referential adverbs via transitional structures, reflecting the grams steadily growing role in expressing not only the spatial relation between the trajector and the landmark but also the landmark itself. The analysis suggests that at least some of the grams that express location are used not only as adpositions and adverbs but also in a referential function. Grams that express containment are convenient for this purpose, because they include information that the landmarks have limits: locating a trajector inside them is safe even in contexts where lexical information is scanty. Krista Ojutkangas - - - - - - - - - - - - Mihin suomessa tarvitaan sis-grammeja? Suomen kieless sisltyvyytt ja vljemmin kiinte yhteytt ilmaistaan tavallisesti sispaikallissijoilla, mutta kieless on mys sarja sis-kantaisia paikkaa ilmaisevia postpositioita ja adverbeja, lyhyesti sis-grammeja. Tutkimuksessani selvitn ensinnkin, millaisten konkreettisten tilasuhteiden kuvauksessa sis-grammit esiintyvt ja miten ne eroavat sispaikallissijojen kytst. Toiseksi tarkastelen sis-grammin kyttyhteyksi jatkumona ja tuon esiin tulkintamahdollisuuden, ett postpositiona ja adverbina toimimisen lisksi niill on mys viittaavaksi tulkittavaa kytt. Kirjoitukseni teoreettisena taustana toimii kognitiivinen kielentutkimus. Sis-grammeilla ilmaistussa tilasuhteessa on relevanttia tietoa nimenomaan kiintopiste-silin sisosa, ikn kuin silin kuorista vlittmtt. Niinp niill kuvataan tilanteita, joissa muuttujan ja kiintopisteen vlinen sisltyvyyssuhde on jollakin tavoin poikkeuksellinen (ruoka suussa suun sisll). Sis-grammeja kytetn mys silloin, kun sispaikallissija saman tilanteen kuvauksessa ilmaisikin kiinte yhteytt sisltyvyyden sijaan (kivi maassa maan sisss). Sis-grammeilla on mahdollista mys puhua siliin sellaisista kappaleista, jotka eivt luontaisesti ole lainkaan silmisi (preen sisll, vrt. preess ’preen pinnassa’). Aineistosta nousee esiin kolme tyypillist kontekstia, joissa sis-grammeja kytetn: sijainnin kuvaamisessa tarkasti, kontrastin ilmaisemisessa kahden paikan vlill ja muuttujan sijoittamisessa kiintopisteeseen sellaisessa ympristss, jossa kiintopiste-sili on ensin tekstiss rakennettu. Grammien syntaktisten kyttympristjen pohjalta voi hahmotella adpositioista vlittvien rakenteiden kautta paljaaseen, viittaavaan adverbiin etenevn jatkumon; jatkumomaisuus syntyy siit, ett eri yhteyksiss grammin vastuu mys kiintopisteen ilmaisemisesta kasvaa vhitellen. Tarkastelun perusteella voi olettaa, ett ainakin osa paikkaa ilmaisevista grammeista toimii paitsi adpositiona ja adverbina mys viittaavassa tehtvss. Sisltyvyytt ilmaisevat grammit ovat thn otollisia, koska ne sisltvt tiedon siit, ett siliill on rajat: muuttujan sijoittaminen niiden sisn on turvallista leksikaalisesti niukemmassakin kontekstissa. Krista Ojutkangas